2021
DOI: 10.1021/acsomega.1c05046
|View full text |Cite
|
Sign up to set email alerts
|

Critical Insight into Plausible Acquired Tocopherol Pathway in Neglected Human Trypanosomatids

Abstract: Despite global therapeutic advancements, tropical parasitic infections like trypanosomiasis and leishmaniasis continue to be a major health concern in developing countries. These two tropical infectious diseases lead to enormous economic loss, significant disability, and morbidity, accounting for over one million deaths per year worldwide. The causative parasites, which shuttle between an insect vector and a mammalian host, thrive either in the bloodstream or in the intramacrophage environments. Essentially, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Interestingly, it has been seen that intracellular parasites, including the RBC-infecting Plasmodium falciparum , are capable of synthesizing tocopherol as a defense mechanism against oxidative stress. …”
Section: Antioxidant Systems In Rbcsmentioning
confidence: 99%
“…Interestingly, it has been seen that intracellular parasites, including the RBC-infecting Plasmodium falciparum , are capable of synthesizing tocopherol as a defense mechanism against oxidative stress. …”
Section: Antioxidant Systems In Rbcsmentioning
confidence: 99%
“…CPB can also modulate host immune responses like the Th1 immune response [46]. TAT enzyme is a known target of TI 4 and is involved in the tocopherol pathway and methionine‐related pathways [17,47]. CPA and CPB expression were three‐ to four‐fold higher, whereas TAT had an upregulation of eight‐fold.…”
Section: Resultsmentioning
confidence: 99%
“…From earlier studies, TI 4 has been suggested to target TAT, which is an important enzyme for stress responses [64]. In addition, the tocopherols, which are important ROS scavengers in several organisms [47], were reduced drastically upon TI 4 treatment. Based on this information, we evaluated the ROS accumulation inside the parasite.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation